2010
DOI: 10.1248/bpb.33.556
|View full text |Cite
|
Sign up to set email alerts
|

Buthionine Sulfoximine Promotes Methylglyoxal-Induced Apoptotic Cell Death and Oxidative Stress in Endothelial Cells

Abstract: Methylglyoxal (MG) is a reactive dicarbonyl compound that is formed as a metabolic byproduct of glycolysis. 1,2) MG is found at high levels in the blood of diabetic patients. 3) MG causes nonenzymatic glycation of proteins to yield irreversible advanced glycation end products (AGEs), leading to cross-linking or degradation of proteins. 4) MG has been linked to the development of diabetic complications related to vascular injury. [3][4][5] MG might contribute to not only the development of diabetes but also the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The loss of EC number and function in diabetes is well described ( 31 ) and largely occurs due to the accumulation of MG ( 32 , 33 ). In our study, the detrimental effect of hyperglycemia on ECs was evident: the number of vWF + and CD31 + ECs was reduced in the hearts of WT-diabetic mice, and neuregulin and eNOS expression was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of EC number and function in diabetes is well described ( 31 ) and largely occurs due to the accumulation of MG ( 32 , 33 ). In our study, the detrimental effect of hyperglycemia on ECs was evident: the number of vWF + and CD31 + ECs was reduced in the hearts of WT-diabetic mice, and neuregulin and eNOS expression was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that MGO impairs HIF-1α degradation and signaling 19,20 and activates AMPK mediated autophagic degradation of thioredoxin 1 21 , thus emphasizing its influence on redox homeostasis 22 . Despite the clear association between reactive carbonyl species and diabetic complications, their mode of action on endothelial cells is discussed ambiguously 2327 . A general finding throughout all studies is however that MGO causes endothelial damage, albeit that different MGO concentrations have been reported at which this occurs 23,2830 .…”
Section: Introductionmentioning
confidence: 99%
“…GSH is reported to have a protective effect against brain vascular endothelial dysfunction, including endothelial barrier permeability [ 19 ], cell death [ 20 ], and the scavenging of ROS [ 21 ]. GSH depletion elicits endothelial oxidative stress and cell apoptosis [ 20 , 22 ]. Some clinical studies demonstrate that an increased risk for stroke is associated with low levels of GSH in the brain [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%